Report of the 4th European Zebrafish Principal Investigator Meeting - Lopes, S; Distel, M; Linker, C; Fior, R; Monteiro, R; Bianco, I; Portugues, R; Strähle, U; Saúde, L (Mary Ann Liebert Publishers, 2016)
The European Zebrafish Principal Investigator Meeting (EZPM) is an ideal forum for group leaders using this fantastic animal model not only to discuss science but also to strengthen their interactions, to push forward technological advances, and to define guidelines for the use of this fish in research. The city of Lisbon (Portugal) was voted by the European group leaders to be the setting for the 4th EZPM, and the organizing committee, composed by Leonor Saúde (iMM Lisboa, PT), Susana Lopes (CEDOC, PT), Michael Orger (Champalimaud Foundation, PT), Rui Oliveira (ISPA, PT), and António Jacinto (CEDOC, PT), was very enthusiastic to organize a productive event. The 4th EZPM took place from March 15 to 19 at Pavilhão do Conhecimento, a Science Museum and Educational Center winner of The Great Prize FAD of Arquitecture 1999 and The Society for Environmental Graphic Design Award 2011. Over 5 days, 135 group leaders (89 men and 46 women) coming from 19 different European countries and also from the United States, Turkey, Israel, Chile, and Singapore presented and discussed their recent research achievements. In addition to the scientific oral and poster presentations, the group leaders gathered in very lively community sessions on morphants versus mutants (chaired by Didier Stainier, Max Planck Institute for Heart and Lung Research, DE), funding issues (chaired by Uwe Strahle, KIT-ITG, DE), and gender equality (chaired by Corinne Houart, KCL, United Kingdom). One of the highlights of the 4th EZPM was the guided visit to Oceanário de Lisboa, an international award-winning place that celebrates life with a stunning display of living aquatic creatures.